Business Continuity - Speight, Peter (Journal of applied security research, 2011)
Business continuity is a management process that identifies potential factors that threaten an organization and provides a framework for building resilience and the capability for an effective response. This response must safeguard the interests of its key stakeholders, as well as the organization's reputation, brand, and value-creating activities. Business continuity management is the subject of continuing development and research. In the United Kingdom, some aspects of business continuity management are covered by legislation; others are covered by industry safety standards such as the British Standard Code of Practice, BS25999 (first issued in 2006 and now incorporating various subsequent updates and supporting documents). This article considers "the mitigation of emergencies, crises and disasters" in more detail, first defining what can be considered to be a major disaster and then examining how organizations can respond to disasters. The more recently developed business continuity management techniques for ensuring that organizations are prepared and resilient, including the use of risk assessment and business continuity planning and the importance of crisis management plans will then be discussed.